2017
DOI: 10.1021/acs.jafc.7b04666
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Specific Effects of Short-Chain Fatty Acids on Plasma Cholesterol Concentration in Male Syrian Hamsters

Abstract: Previous studies have shown that short-chain fatty acids (SCFAs) are capable of decreasing plasma cholesterol. However, the relative plasma-cholesterol-lowering activity of individual SCFAs and the underlying mechanisms by which SCFAs decrease plasma cholesterol remain largely unknown. The present study was done to compare the plasma-cholesterol-lowering potencies of four common SCFAs with 2-5 carbons and to investigate their interactions with gene expressions of key regulatory factors involved in cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 33 publications
5
78
3
1
Order By: Relevance
“…A similar rise in Cyp7a was observed in Apoe-deficient mice fed with a cholesterolrich diet supplemented with butyrate, with additional beneficial effects on the "reverse cholesterol transport" (RCT) (Du et al, 2019). The connection between SCFAs and BAs metabolism was further reported in Syrian hamsters (Zhao et al, 2017). The addition of acetate, propionate, or butyrate to a cholesterol-rich diet resulted in decreased CT levels and LDL-C/HDL-C ratio and to increased fecal excretion of BAs (LCA, DCA, CDCA, CA).…”
Section: Short-chain Fatty Acids (Scfas)supporting
confidence: 55%
See 2 more Smart Citations
“…A similar rise in Cyp7a was observed in Apoe-deficient mice fed with a cholesterolrich diet supplemented with butyrate, with additional beneficial effects on the "reverse cholesterol transport" (RCT) (Du et al, 2019). The connection between SCFAs and BAs metabolism was further reported in Syrian hamsters (Zhao et al, 2017). The addition of acetate, propionate, or butyrate to a cholesterol-rich diet resulted in decreased CT levels and LDL-C/HDL-C ratio and to increased fecal excretion of BAs (LCA, DCA, CDCA, CA).…”
Section: Short-chain Fatty Acids (Scfas)supporting
confidence: 55%
“…Ex vivo and in vivo studies have shown that acetate and butyrate (but not propionate) are potential precursors of cholesterol synthesis that can be incorporated into the endogenous cholesterol synthesis pathway (Wolever et al, 1991;Demigné et al, 1995;den Besten et al, 2013). By contrast, earlier studies reported inhibition of cholesterol synthesis by propionate through decreased expression of the HMGCS and HMGCR genes (Bush and Milligan, 1971;Rodwell et al, 1976;Demigné et al, 1995), white more recent studies have not confirmed such effects (Zhao et al, 2017). Accordingly, in healthy subjects, the oral administration of propionate does not lower plasma cholesterol but does increase HDL and triglycerides levels (Venter et al, 1990).…”
Section: Short-chain Fatty Acids (Scfas)mentioning
confidence: 94%
See 1 more Smart Citation
“…However, this association does not hold for the HFD-fed animals since ABCG5/G8 mRNA levels were increased in these groups of rats. It is likely that other mechanisms such as fecal excretion of biliary acids (27) or increased synthesis and secretion of VLDL are involved Other important questions that emerge from the present results are what factors alter the expression of key metabolic markers of hepatic cholesterol homeostasis in response to 2 weeks of WD, and why does the response in animals submitted to the HFD not reach the same extent? It must be taken into account that after 2 weeks, hepatic TG levels were higher in WD-than in HFD-fed rats, and this might have interfered with cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 94%
“…However, this association does not hold for the HFD-fed animals since ABCG5/G8 mRNA levels were increased in these groups of rats. It is likely that other mechanisms such as fecal excretion of biliary acids [27] or increased synthesis and secretion of VLDL are involved.…”
Section: Discussionmentioning
confidence: 99%